[tex]\left\{\begin{matrix}
\frac{x}{3} + \frac{y}{2} = 1 \: | \times 6\\ \\
2(x + 1) + y = 4\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
2x + 3y = 6\\
2x + 2 + y = 4\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
2x + 3y = 6\\
2x + y = 4 - 2\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
2x + 3y = 6\\
2x + y = 2\end{matrix}\right.[/tex]
[tex]2x + y = 2[/tex]
[tex]y = 2 - 2x[/tex]
[tex]2x + 3y = 6[/tex]
[tex]2x + 3(2 - 2x) = 6[/tex]
[tex]2x + 6 - 6x = 6[/tex]
[tex]2x - 6x = 6 - 6[/tex]
[tex] - 4x = 0 \: | \times ( - 1)[/tex]
[tex]4x = 0[/tex]
[tex]x = \frac{0}{4} [/tex]
[tex]x = 0[/tex]
[tex]y = 2 - 2x[/tex]
[tex]y = 2 - 2 \times 0[/tex]
[tex]y = 2 - 0[/tex]
[tex]y = 2[/tex]